(3x+17)+(x-23)=9

Simple and best practice solution for (3x+17)+(x-23)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+17)+(x-23)=9 equation:


Simplifying
(3x + 17) + (x + -23) = 9

Reorder the terms:
(17 + 3x) + (x + -23) = 9

Remove parenthesis around (17 + 3x)
17 + 3x + (x + -23) = 9

Reorder the terms:
17 + 3x + (-23 + x) = 9

Remove parenthesis around (-23 + x)
17 + 3x + -23 + x = 9

Reorder the terms:
17 + -23 + 3x + x = 9

Combine like terms: 17 + -23 = -6
-6 + 3x + x = 9

Combine like terms: 3x + x = 4x
-6 + 4x = 9

Solving
-6 + 4x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4x = 9 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 9 + 6
4x = 9 + 6

Combine like terms: 9 + 6 = 15
4x = 15

Divide each side by '4'.
x = 3.75

Simplifying
x = 3.75

See similar equations:

| 5x^4-44x^2+22=0 | | 2.5X+2.5X=10 | | g(3)=3x^2+1 | | 9(d-4)-8+2d=5d-4+2d | | 4x=(20x-8) | | X=25.6+-1.4Y | | (3x+17)+(4x-5)=90 | | 5+2(x)=3(x)-2 | | 0.6=0.5+25 | | 0.25X+0.35Y=6.4 | | 15-9x/3 | | 8-0.6+8= | | 9=n/m | | 1n+1m=x | | f(6)=4x-10 | | 4a+7=2a | | 2x-14+4=10 | | B=540-30*m | | 1x+2y+3z=34 | | X^2-10=11 | | (2x+50)+x+x=180 | | X^2=a^2 | | 4x+11=20-2 | | 5x=560+1.04x | | 4x^3-6x^3-2x+5=0 | | x^2+(x^2+2)=100 | | 12-10z+5x=-18 | | -15+3c-7c=-43 | | log(2x+1)log(2x-1)=1 | | 10=-7v+4(v+4) | | log(2x-12)=4 | | 2d+8=32 |

Equations solver categories